Effect of Docosahexaenoic Acid on Cell Cycle Pathways in Breast Cell Lines With Different Transformation Degree. Issue 6 (26th October 2015) - Rescigno, Tania; Capasso, Anna; Tecce, Mario Felice
Abstract : n‐3 polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), abundant in fish, have been shown to affect development and progression of some types of cancer, including breast cancer. The aim of our study was to further analyze and clarify the effects of these nutrients on the molecular mechanisms underlying breast cancer. Following treatments with DHA we examined cell viability, death, cell cycle, and some molecular effects in breast cell lines with different transformation, phenotypic, and biochemical characteristics (MCF‐10A, MCF‐7, SK‐BR‐3, ZR‐75‐1). These investigations showed that DHA is able to affect cell viability, proliferation, and cell cycle progression in a different way in each assayed breast cell line. The activation of ERK1/2 and STAT3 pathways and the expression and/or activation of molecules involved in cell cycle regulation such as p21 Waf1/Cip1 and p53, are very differently regulated by DHA treatments in each cell model. DHA selectively: (i) arrests non tumoral MCF‐10A breast cells in G0 /G1 cycle phase, activating p21 Waf1/Cip1, and p53, (ii) induces to death highly transformed breast cells SK‐BR‐3, reducing ERK1/2 and STAT3 phosphorylation and (iii) only slightly affects each analyzed process in MCF‐7 breast cell line with transformation degree lower than SK‐BR‐3 cells. These findings suggest a more relevant inhibitory role of DHA within early development and late progression of breast cancer cell transformation and a variable effect in the other phases, depending on individual molecular properties and degree of malignancy of each clinical case. J. Cell. Physiol. 231: 1226–1236, 2016. © 2015 Wiley Periodicals, Inc.